The Influence of Role Playing Learning Model on Learning Outcomes of Speaking Skills in Simple Interviewing for Fifth Grade Students of SDN 2 Tambakrigadung Lamongan - Mochammad Miftachul Huda; Ahmad Ipmawan Kharisma; Nur Fathin Afifah (CV. Jendela Edukasi Indonesia, 2022)
The purpose of this study is to see how the role playing learning model affects students' speaking skills in class 5C SDN 2 Tambakrigadung Lamongan. This is a quantitative study that use the Posttest-Only Control Design approach. The data was collected using a random sampling technique and a learning outcome test in the form of a description (conversational text). The two-sample paired t-test formula was used for hypothesis testing. With 39 students in each class, the sample comprised of two classes: class 5C as the experimental group and class 5A as the control group. The results of the data analysis revealed that the role playing model had an effect on the speaking abilities of 5th grade students at SDN 2 Tambakrigadung Lamongan.The results of the data analysis revealed that the value of tcount was bigger than ttable, or 5.80 > 1.665 at a significance level of 5%, hence H0 was rejected and Ha was given.